2020
DOI: 10.1186/s12978-020-0893-4
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal examination of changing fertility intentions and behaviors over a four-year period in urban Senegal

Abstract: Background: Fertility intentions and contraceptive use are often used to demonstrate gaps in programs and policies to meet the contraceptive needs of women and couples. Prior work demonstrated that fertility intentions are fluid and change over a woman's (or couple's) life course with changing marital status, childbearing, and education/employment opportunities. This study uses longitudinal data to better examine the fluidity of women's fertility intentions and disentangle the complex interrelationships betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…18 Further, many women have ambivalent fertility desires (i.e., are undecided about future childbearing or the timing of future childbearing). 19 Such women may be misclassified as having an unmet need when indeed they have no desire or intention to use a method in the future and may welcome an "unexpected" pregnancy, [20][21][22] although the majority of women with unintended pregnancies obtain abortions. 23 As noted previously, problems with language that is currently used to describe need-related indicators are further illustrated through the label of "demand satisfied" for contraception and especially "demand satisfied for modern methods."…”
Section: Challenges With Language and Use Of Need-based Measuresmentioning
confidence: 99%
“…18 Further, many women have ambivalent fertility desires (i.e., are undecided about future childbearing or the timing of future childbearing). 19 Such women may be misclassified as having an unmet need when indeed they have no desire or intention to use a method in the future and may welcome an "unexpected" pregnancy, [20][21][22] although the majority of women with unintended pregnancies obtain abortions. 23 As noted previously, problems with language that is currently used to describe need-related indicators are further illustrated through the label of "demand satisfied" for contraception and especially "demand satisfied for modern methods."…”
Section: Challenges With Language and Use Of Need-based Measuresmentioning
confidence: 99%
“…Diversity is a major strength in the cohort with about equal representation among Black and non-Black women. Self-reported reproductive plans are linked to future reproduction, albeit imperfectly [ 58 , 59 ]. To create the adolescent pregnancy variable, we used self-reported age at first pregnancy, because self-reported maternal age has been established as reliable as medical records [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors include experiencing an unintended pregnancy, having partner’s support, being older in age, achieving a desired number of children, higher number of living children, higher number of male children, being in school or working, and discussing FP with a friend [ 6 , 7 , 9 , 11 13 ]. Fertility intentions (the desire for a certain number of children and the intended timing of a first birth and subsequent spacing between births [ 14 ]) have also been shown to be associated with contraceptive use [ 15 ] and continuation [ 12 , 13 ]. Yet women’s fertility intentions can and often change, even within a short period of time [ 15 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fertility intentions (the desire for a certain number of children and the intended timing of a first birth and subsequent spacing between births [ 14 ]) have also been shown to be associated with contraceptive use [ 15 ] and continuation [ 12 , 13 ]. Yet women’s fertility intentions can and often change, even within a short period of time [ 15 – 17 ]. For example, one study in the US has found that while 39% of women who were interviewed three times within a year reported being uncertain if they wanted more children, only 9% consistently reported uncertainty [ 16 ].…”
Section: Introductionmentioning
confidence: 99%